A new method using Scanning Electron Microscopy (SEM) for preparation of anisopterous odonates - del Palacio, Alejandro (2017)
Anisopterous odonate male's secondary genitalia is a complex of several structures, among them the vesica spermalis is the most informative with important specific characters. The observation of those characters, mostly of membranous nature, is difficult in the Scanning Electron Microscope due to dehydration and metallization processes. In this contribution, we discuss a new and low cost procedure for the observation of these characters in the SEM, compatible with the most common agents used for preserving specimens.